The impact of patient choice on survival in chronic thromboembolic pulmonary hypertension. Issue 3 (16th September 2018) - Quadery, Syed Rehan; Swift, Andrew J.; Billings, Catherine G.; Thompson, Alfred A.R.; Elliot, Charles A.; Hurdman, Judith; Charalampopoulos, Athanasios; Sabroe, Ian; Armstrong, Iain J.; Hamilton, Neil; Sephton, Paul; Garrad, Sian; et al.
Pulmonary endarterectomy (PEA) is the gold standard treatment for operable chronic thromboembolic pulmonary hypertension (CTEPH). However, a proportion of patients with operable disease decline surgery. There are currently no published data on this patient group. The aim of this study was to identify outcomes and prognostic factors in a large cohort of consecutive patients with CTEPH. Data were collected for consecutive, treatment-naive CTEPH patients at the Pulmonary Vascular Disease Unit of the Royal Hallamshire Hospital (Sheffield, UK) between 2001 and 2014. Of 550 CTEPH patients (mean±sd age 63±15 years, follow-up 4±3 years), 49% underwent surgery, 32% had technically operable disease and did not undergo surgery (including patient choice n=72 and unfit for surgery n=63), and 19% had inoperable disease due to disease distribution. The 5-year survival was superior in patients undergoing PEA (83%) versus technically operable disease who did not undergo surgery (53%) and inoperable due to disease distribution (59%) (p<0.001). Survival was superior in patients following PEA compared with those offered but declining surgery (55%) (p<0.001). In patients offered PEA, independent prognostic factors included mixed venous oxygen saturation, gas transfer and patient decision to proceed to surgery. Outcomes in CTEPH following PEA are excellent and superior to patients declining surgery, and strongly favour consideration of a surgical intervention in eligible patients. Outcomes for patients undergoing pulmonary endarterectomy are excellent and superior to patients declining surgery http://ow.ly/9UZw30kA28m